The Effect Of Listening While Reading (LWR) on Students Reading Fluncy at Second Grade Students of State Senior High School 1 Janapria - Lia Opiani (Graduate Program, University of Islam Malang, 2019)
AbstractThe research was conduct to measure the effect of listning while reading to promote students reading fluency. Quasi-experimental applied in this study and the sample was all second grade students of senior high school 1 JANAPRIA in academic years 2018/2019. The sample this study was two classes of second grade students of senior high school JANAPRIA. Class XI IPS II was the experimental group and class XI IPS I was the control group. the result of Independent T-test computation of post-test showed that Tobt for reading comprehension was (t=8.958) was the same with Tcrit was (t=8.958) and for reading rate Tobt was (t=13.739) and was the same with Tcrit was (t=13.739)and the value significance for reading comprehension and rate were .000 hence, due to the sig (2-tailed) .000<.0.05 means that there were significantly different between the post-test scores of experimental group and control group after treatment. Hence, it can be concluded that the level of significant of LWR and conventional method are significantly different. Overall, the students who are taught using listening while reading had better on reading fluency than those who are not.Key words: Reading Fluency, Listening while Reading (LWR), Narrative text.